Rehabilitasi Pendidikan Indonesia Melalui Konsep Pendidikan Humanisme Ki Hajar Dewantara [Rehabilitation of Indonesian Education Through Ki Hajar Dewantara's Concept of Humanist Education] - Kristanto, Yenny; Faritz Bahan; Renovan Nache (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2025)
Education stands as the foundation for nurturing and touching each soul then turns it into a compassionate one. Through learning, students are guided to uncover and fulfill their unique identities and potential optimally. When education focuses only on intellectual achievement, it risks detaching learners from their communities. In Indonesia, this imbalance has been stark, while cognitive development is prioritized, emotional and creative, and character-building dimensions often receive little attention. The high incidence of student violence that continues reflects a deeper crisis that one rooted not in academic shortcomings alone, but in the absence of holistic character education. Therefore, this study aims to examine how Ki Hajar Dewantara’s principles offer meaningful responses to today’s challenges and how it can be integrated with the existing and modern educational frameworks. Through this paper, the author conducts research based on literature review using a three-step method (theoretical, reflective, and applicative) to delve into the humanistic philosophy of education by Ki Hajar Dewantara. By anchoring the research in Ki Hajar Dewantara’s holistic approach, this study hopes to contribute toward reviving our national education identity, where academic excellence intersects with emotional intelligence, cultural rootedness and moral integrity.